2017
DOI: 10.1007/jhep10(2017)039
|View full text |Cite
|
Sign up to set email alerts
|

A supersymmetric electroweak scale seesaw model

Abstract: In this paper we propose a novel supersymmetric inverse seesaw model which has only one additional Z 6 symmetry. The field content is minimal to get a viable neutrino spectrum at tree-level. Interestingly, the inverse seesaw scale in our model is related to the scale of electroweak symmetry breaking. Due to that origin we are less biased about hierarchies and discuss three different types of the inverse seesaw mechanism with different phenomenologies. We can successfully reproduce neutrino masses and mixing an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…This is another economic model that naturally suppresses the DM-nucleon scattering. In fact, given that the neutralino DM has been tightly limited by the DD experiments in recent years, the sneutrino DM embedded in different extensions of the MSSM has regained broad interest [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…This is another economic model that naturally suppresses the DM-nucleon scattering. In fact, given that the neutralino DM has been tightly limited by the DD experiments in recent years, the sneutrino DM embedded in different extensions of the MSSM has regained broad interest [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…We showed by both analytic formulas and numerical calculations that the resulting theory (abbreviated as ISS-NMSSM hereafter) was one of the most economic framework to generate the neutrino mass and, meanwhile, to reconcile the DM DD experiments naturally [8,14]. We add that, besides us, a lot of authors have showed interest in the sneutrino DM in recent years [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], but none of them considered the same theoretical framework as ours.…”
Section: Introductionmentioning
confidence: 83%
“…One is that in the Type-I extension, the sneutrino DM is a roughly pure right-handed sneutrino state, while in the inverse seesaw extension, it is a mixture of νL , νR and X with the last two components being dominated. Consequently, the DM physics in the inverse seesaw extension is more complex [48][49][50]. The other is that in both the extensions, CP-even and CP-odd sneutrino states split in mass due to the presence of lepton number violating interactions.…”
Section: Arxiv:180703762v3 [Hep-ph] 30 May 2019mentioning
confidence: 99%
“…It has long been known that the fieldŜ plays an extraordinary role in the model: solving the µ problem of the MSSM [38], enhancing the theoretical prediction about the mass of the SM-like Higgs boson [39][40][41] as well as enriching the phenomenology of the NMSSM (see for example [42][43][44][45][46][47]). In this context we stress that, in the seesaw extension of the NMSSM, it is also responsible for heavy neutrino mass and the annihilation of sneutrino DM [48][49][50], and consequently makes the sneutrino DM compatible with various measurements. The underlying reason for the capability is that the newly introduced heavy neutrino fields in the extension are singlets under the gauge group of the SM model, so they can couple directly withŜ.…”
Section: Introductionmentioning
confidence: 99%